Incidence of attrition and predictors among HIV-infected adolescents receiving antiretroviral therapy in public hospitals, South Ethiopia: a multicentre retrospective follow-up study - Temesgen Mohammed Toma; Tamirat Gezahegn Guyo; Abraham Anbesie Sapo; Fasika Merid; Serekebirahan Sahile; Simegn Wagaye Kefene (BMJ Open)
Objective This study aimed to determine the incidence of attrition and its predictors among HIV-infected adolescents receiving antiretroviral therapy in public hospitals, South Ethiopia.Study design A multicentre retrospective follow-up study was conducted, and Cox proportional hazards model was used to identify predictors of the study outcome variable (attrition).Settings The study was conducted in eight public hospitals (two general and six primary hospitals) in South Ethiopia.Participants Adolescents (10–19 years) on antiretroviral therapy from 1 January 2014 to 30 December 2023 (n=409). The data were collected from patients’ charts and electronic data records.Outcome variable The primary outcome was time to attrition, and the secondary outcome was predictors of attrition.Results The overall incidence density of attrition was 3.33 (95% CI: 2.65 to 4.18) per 100 person-year of observation. Age 15–19 years (adjusted HR (AHR): 1.88; 95% CI: 1.12 to 3.18), death of both the parents (AHR: 2.19; 95% CI: 1.04 to 4.61), no formal education (AHR: 3.16; 95% CI: 1.48 to 6.77), Co-trimoxazole Prophylactic Therapy (CPT) non-utilisation (AHR: 1.73; 95% CI: 1.03 to 2.91), not changed regimen (AHR: 6.16; 95% CI: 3.56 to 10.66) and poor treatment adherence (AHR: 5.16; 95% CI: 2.35 to 11.32) were predictors of attrition.Conclusion Attrition was identified to be a significant public health problem in study settings. Moreover, old age, parental death, not attending formal education, not using CPT, unchanged baseline regimen and suboptimal treatment adherence predict attrition. Hence, special attention should be given to older adolescents, those with no formal education, orphaned and with poor baseline clinical characteristics. Likewise, early tracing of missed follow-up schedules, improving adherence support and increasing contacting frequency to reduce attrition are highly encouraged.